Study Of Health Profile of Residents of Geriatric Home in Ahmedabad District - Banker, Kavita; Prajapati, Bipin; Kedia, Geeta (National Journal of Community Medicine, 2011)
Background: Aging is a normal process. The modernization plays a vital role in aging process of an individual. The aged feel a sense of social isolation because of disjunction from various bonds viz work relationships, and diminish of relatives and friends, mobility of children to far off places for jobs. The situation of the elderly still worsens when there is presence of chronic diseases, physical incapacity and financial stringency. Objective: To know the health profile and health related problems of the old age inmates residing at geriatric homes. Material and Methods: A cross sectional study was carried out in geriatric homes of urban and peri urban areas of Ahmedabad during January 2008 to January 2009. Result: Out of total 530 inmates, 45.85% were males and 54.15% were females. 93.77% reported one or more health related complaints. 37.4% were obese and 11.9% were underweight. Most common presenting symptoms were: loss of teeth (70%), joint pain (60.2%), impaired vision (44.2%), weakness (34.9%), and insomnia (34%). 82.3% were using spectacles followed by walking sticks (21.7%) and denture (12.8%). The main health related problems were osteoarthritis (54.9%), hypertension (54.2%), cataract (16%) and diabetes mellitus (14.9%). Conclusion: The study highlighted a high prevalence of morbidity and health related problems in old age groups. We need to strengthen geriatric health care services, social support by people, proper implementation of geriatric related legislation by government and further research like qualitative research to explore the problems of the elderly.